2022
DOI: 10.1186/s13072-022-00463-6
|View full text |Cite
|
Sign up to set email alerts
|

PDS5A and PDS5B differentially affect gene expression without altering cohesin localization across the genome

Abstract: Background Cohesin is an important structural regulator of the genome, regulating both three-dimensional genome organization and gene expression. The core cohesin trimer interacts with various HEAT repeat accessory subunits, yielding cohesin complexes of distinct compositions and potentially distinct functions. The roles of the two mutually exclusive HEAT repeat subunits PDS5A and PDS5B are not well understood. Results Here, we determine that PDS5A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 72 publications
(152 reference statements)
2
2
0
Order By: Relevance
“…Based on this classification, our transcriptome analysis revealed that PRC1/PRC2 target gene expression was significantly increased in both Pds5a GT KO ESCs and Pds5a KO ESCs (Fig. 2c, d ), in agreement with a recent report 50 . Consistent with derepression of PRC1/PRC2 target genes, Gene Ontology (GO) analysis of upregulated genes revealed terms related to developmental processes such as neurogenesis and pattern specification (Fig.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Based on this classification, our transcriptome analysis revealed that PRC1/PRC2 target gene expression was significantly increased in both Pds5a GT KO ESCs and Pds5a KO ESCs (Fig. 2c, d ), in agreement with a recent report 50 . Consistent with derepression of PRC1/PRC2 target genes, Gene Ontology (GO) analysis of upregulated genes revealed terms related to developmental processes such as neurogenesis and pattern specification (Fig.…”
Section: Resultssupporting
confidence: 92%
“…As expected, PDS5A showed extensive overlap with RAD21 and CTCF (Supplementary Fig. 4a–d ) 50 , 58 , 59 . In contrast, PDS5A was absent from Polycomb target genes, suggesting that PDS5A indirectly promotes silencing of PRC1/PRC2 target genes (Supplementary Fig.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations